2013
DOI: 10.1177/1069072713498685
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Evaluation of Schein’s (1985) Career Orientations Inventory

Abstract: Since its introduction, Schein’s Career Orientations Inventory (COI) has been widely used to assess and advise individuals who are making both initial and specialty career choices. Employed by both practitioners and researchers, the COI was designed to identify the person’s “career anchors,” also known as their career identities. Individuals are expected to have the highest job satisfaction and performance when their job specialization matches their career anchors. However, little published research has evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
16
0
3
Order By: Relevance
“…Selain disebabkan oleh maraknya perusahaan berjenis hospitality, masyarakat Bali juga memaknai pekerja-annya dengan berbeda. Pemilihan karier seseorang biasanya ditandai dengan ketertarikannya dalam bidang karier tertentu yang merepresentasikan identitas pribadi atau citra diri (Leong, Rosenberg & Chong, 2014). Masyarakat Bali yang sudah terkenal dengan keramahtamahannya biasanya juga akan memilih jenis karier yang memiliki unsur keramahtamahan didalam-nya.…”
Section: Hasilunclassified
“…Selain disebabkan oleh maraknya perusahaan berjenis hospitality, masyarakat Bali juga memaknai pekerja-annya dengan berbeda. Pemilihan karier seseorang biasanya ditandai dengan ketertarikannya dalam bidang karier tertentu yang merepresentasikan identitas pribadi atau citra diri (Leong, Rosenberg & Chong, 2014). Masyarakat Bali yang sudah terkenal dengan keramahtamahannya biasanya juga akan memilih jenis karier yang memiliki unsur keramahtamahan didalam-nya.…”
Section: Hasilunclassified
“…According to Leong, Rosenberg and Chong (2013), individuals should have higher job satisfaction when the job specialization corresponds to their career anchor. A tool can also help management to take note of the various career orientations of employees and use to select the employee for the most suitable working position (Igbaria et al, 1999).…”
Section: Career Anchors and Job Satisfactionmentioning
confidence: 99%
“…Considering these findings, this study has the following aims: to conduct the first Schein COI study in Colombia to provide new insights into this model in developing countries; to provide an open access data-driven study, and hence, address the evidence gap identified by Barclay et al (2013), for which they found that only seven out of 90 studies contained the detailed information required (e.g. correlation matrix between the CAs); and to address the methodological gap indicated by Leong et al (2014) that is related to the fewer studies in which exploratory and confirmatory factor analysis were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…we provided an open access data-driven study; and we addressed the methodological gap indicated by Leong et al (2014) related to the fewer studies in which exploratory and…”
mentioning
confidence: 99%